2019
DOI: 10.1080/0886022x.2019.1633350
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxidative stress-mediated apoptosis in the pathogenesis of uric acid nephropathy

Abstract: Objective: By copying the uric acid nephropathy rat model, the oxidative stress injury of mitochondria was caused in renal tubular epithelial cells and the relationship between the injury and the induction of cell apoptosis was identified. Methods: All rats were randomly divided into NC (normal control, NC) group, HUA (high uric acid, HUA) group and GSH (reductive glutathione, GSH) group. The values were quantitatively tested in the kidney tissues, including 24-h urinary prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 17 publications
3
34
2
1
Order By: Relevance
“…For example, the vehicle utilized to formulate the PAHSA is critical not only to assure bioavailability and safety but also to avoid masking the effects of PAHSA. In NASH, in addition to metabolic disturbance, the accumulation of lipids in hepatocytes, oxidative stress and decreased ATP production trigger mitochondrial dysfunction [18]. In the current work, we showed an additional protective function of 9-PAHSA in an in vitro model of steatosis.…”
Section: Discussionsupporting
confidence: 60%
“…For example, the vehicle utilized to formulate the PAHSA is critical not only to assure bioavailability and safety but also to avoid masking the effects of PAHSA. In NASH, in addition to metabolic disturbance, the accumulation of lipids in hepatocytes, oxidative stress and decreased ATP production trigger mitochondrial dysfunction [18]. In the current work, we showed an additional protective function of 9-PAHSA in an in vitro model of steatosis.…”
Section: Discussionsupporting
confidence: 60%
“…Many studies have shown that hyperuricemia-induced oxidative stress affects multiple organs and systems, including the kidneys [ 42 44 ]. Pathologically, hyperuricemia-associated oxidative stress gives rise to DNA damage, oxidation and inactivation of enzymes, inflammatory cytokine production, and cell apoptosis [ 45 ].…”
Section: Mechanisms Of Hyperuricemia-induced Renal Injurymentioning
confidence: 99%
“…Meanwhile, it has been reported that hyperuricemia induced endothelial dysfunction via regulation of AR, while inhibition of AR or degradation of ROS could restore endothelial function [ 51 ]. Similarly, antioxidant therapies, such as tempol and reduced GSH, may be beneficial for the recovery of endothelial function [ 45 , 46 ]. Taken together, hyperuricemia-mediated oxidative stress directly damages the kidney, thus being a biotherapeutic target for UA-induced renal damage.…”
Section: Mechanisms Of Hyperuricemia-induced Renal Injurymentioning
confidence: 99%
“…The increase in uric acid synthesis damages renal functions, which can be explained by direct promotion of oxidative stress. Increased uric acid synthesis can promote oxidative stress by generating superoxide radicals which can stimulate the mitochondrial membrane lipid peroxidation, mitochondrial dysfunction and cell apoptosis (22).…”
Section: Egfr and Serum Creatininementioning
confidence: 99%
“…The mitochondrial membrane lipid peroxidation occurs when uncontrolled free oxygen radicals are produced. Lipid peroxidation participates in reducing the membrane fl uidity that can lead to mitochondrial swelling, mitochondrial dysfunction, and apoptosis of renal tubule epithelial cells (22). The major sites of mitochondrial ROS generation are at complex I and complex III.…”
Section: Plasma Coq 10-total In Subgroups Of Ckd Patients With Concommentioning
confidence: 99%